The history of nursing profession in ancient Egyptian society - Sameh Elhabashy; Elshaimaa M. Abdelgawad (Elsevier, 2019)
Many of historical textual and epigraphical sources consider medicine as a highly advanced profession in ancient Egypt with little mention of the role of nurses in assistance and supporting this advanced medical care. The purpose of this article is to provide an overview of the history of the profession of nursing in ancient Egypt, and describe the influence of societal trends on the development of nursing. This article discusses nursing as a health care profession in ancient Egyptian civilization. It explains nurses' social background, their working conditions, their professional functions as well as health and illness beliefs that influenced their professional practice. The current article used the historical research design to answer the pre-mentioned questions in the period dated from circa 3100 BCE to the end of the Greco-Roman period 332 BCE-395 CE. The researchers conducted an in-depth review and seeking for information from experts in Egyptology, followed by gathering, drafting, reflecting on, revising, and recording the narrative of evidenced information. Keywords: History, Ancient Egyptian, Nursing, Wet nurse